What do exogenous shocks tell us about growth theories? - Ilan Noy; Aekkanush Nualsri (University of California, Santa Cruz Institute for International Economics (SCIIE), 2007)
The sources of economic growth and development have been puzzling economists from the modern dawn of the profession. While the Solow-Swan neo-classical model dominated research on growth in the 1960s and 1970s, the 1980s saw the emergence of growth theories that disputed, largely on theoretical grounds, the Solow-Swan assumptions and conclusions. In this paper, we do not examine the determinants of the level of per capita income as an indication that a certain theory has better explanatory power. Rather, we focus on the dynamics of growth following external exogenous shocks (natural disasters). We argue that the data analysis we present suggests that the neoclassical model does not accord very well with the growth experience of developing countries.
Keywords: O11; O40; Q54; 330; growth theory; long run growth; Solow; disasters; exogenous shocks; Wachstumstheorie; Entwicklungstheorie; Schock; Naturkatastrophe; Theorie; Schätzung; Entwicklungsländer; OECD-Staaten